Association between obesity and age-related cataract: an updated systematic review and dose–response meta-analysis of prospective cohort studies - Niazi, Sana; Moshirfar, Majid; Dastjerdi, Mohammad H.; Niazi, Feizollah; Doroodgar, Farideh; Ambrósio, Renato (Frontiers in Nutrition, 2024)
Objective: There are inconsistent findings on the association between obesity and age-related cataract (ARC). This systematic review was done to summarize available findings on the association between obesity [defined by body mass index (BMI)] and ARC by performing a dose-response meta-analysis on eligible prospective cohort studies. Methods: We performed a systematic search in PubMed, Scopus, ISI Web of Knowledge, and Google Scholar until June 2022 to identify eligible publications. Results: In total, 16 studies with a total sample size of 1,607,125 participants were included. Among all of these studies, there were 103,897 cases of ARC. In the follow-up periods ranging between 4 and 28 years, 4870 cases of nuclear cataract, 1611 cases of cortical cataract, and 1603 cases of posterior subcapsular cataracts (PSC) were detected. By comparing the highest and lowest categories of BMI, we found that higher BMI was associated with an increased risk of ARC (RR: 1.18, 95% CI: 1.09-1.28) and PSC (RR: 1.44, 95% CI: 1.08-1.90). In the dose-response analysis, each 5 kg/m2 increase in BMI was associated with a 6% and 27% increased risk of ARC (RR: 1.06, 95% CI: 1.01-1.12) and PSC (RR: 1.27, 95% CI: 1.14-1.41), respectively. In addition, we found a positive association for cortical cataract among high-quality studies, in which higher BMI was associated with a 20% increased risk of cortical cataract (RR: 1.20, 95% CI: 1.02-1.42). In terms of nuclear cataract, we found no significant association either in the comparison between the highest and lowest categories of BMI or in the dose-response meta-analysis. Conclusion: Obesity (defined by BMI) was associated with an increased risk of ARC, PSC, and cortical cataract in adults. However, such a positive association was not seen for nuclear cataract. PROSPERO registration: CRD42022357132